Brassinin Induces Apoptosis in PC‐3 Human Prostate Cancer Cells through the Suppression of PI3K/Akt/mTOR/S6K1 Signaling Cascades. (20th May 2013) - Kim, Sung‐Moo; Park, Jeong Ha; Kim, Ki Dong; Nam, Dongwoo; Shim, Bum Sang; Kim, Sung‐Hoon; Ahn, Kyoo Seok; Choi, Seung‐Hoon; Ahn, Kwang Seok
<x xml:space="preserve">Abstract</x> The oncogenic PI3K/Akt/mammalian target of rapamycin (mTOR) signaling axis and its downstream effector, the ribosomal protein S6 kinase 1 (S6K1) play a key role in mediating cell survival in various tumor cells. Here, we investigated the effects of brassinin (BSN), a phytoalexin first identified as a constituent of cabbage, on the PI3K/Akt/mTOR/S6K1 activation, cellular proliferation, and apoptosis in PC‐3 human prostate cancer. BSN exerted a significant dose‐dependent cytotoxicity and reduced constitutive phosphorylation of Akt against androgen‐independent PC‐3 cells as compared to androgen‐dependent LNCaP cells. Moreover, knockdown of androgen receptor (AR) by small interfering RNA enhanced the potential effect of BSN on induction of apoptosis in LNCaP cells. BSN clearly suppressed the constitutive activation of PI3K/Akt/mTOR/S6K1 signaling cascade, which correlated with the induction of apoptosis as characterized by accumulation of cells in subG1 phase, positive Annexin V binding, TUNEL staining, loss of mitochondrial membrane potential, down‐regulation of antiapoptotic and proliferative proteins, activation of caspase‐3, and cleavage of PARP. Additionally, BSN could block broad‐spectrum inhibition of PI3K/Akt/mTOR/S6K1 axes, and aberrant Akt activation by pcDNA3‐myr‐HA‐Akt1 plasmid could not prevent the observed suppressive effect of BSN on constitutive mTOR activation. Finally, overexpression of Bcl‐2 also attenuated BSN‐mediated apoptosis in PC‐3 cells. Taken together, our findings suggest that BSN can interfere with multiple signaling cascades involved in tumorigenesis and might be provided as a potential therapeutic candidate for both the prevention and treatment of prostate cancer. Copyright © 2013 John Wiley & Sons, Ltd.